Rustic Scenery, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
This coloured postcard depicts rustic scenery in Trinidad circa 1911. The fashion of the clothes worn by the three persons standing at the centre of the road is noteworthy. The lady, of African descent, standing on the right is dressed in attire typical of this era: broad-brimmed hat, light pink shirt with leg of mutton sleeve and long skirt that clears the floor - ending near her ankle. Next to her at the left of the photograph is a man in a shirt with tie, pants and hat. He is posing with his bicycle. Behind this pair is a man, of African descent, in an unbuttoned shirt worn over another shirt, pants and he is holding something on his head. The threesome is standing under a spectacular arch made by the tall bamboo that is growing on either side of the road.
Colour: Coloured; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Bamboo--Trinidad and Tobago; Roads--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Bicycles--Trinidad and Tobago; [1912]; Blacks--Trinidad and Tobago; Hats--Trinidad and Tobago; Scenic byways--Trinidad and Tobago